Konsep daring dan luring terhadap hasil belajar IPA siswa SD pada materi sumber energi - Nuri Fitriani; Karta Sasmita; Widiasih Widiasih (Universitas Sarjanawiyata Tamansiswa, 2023)
The Home Learning Program (BDR) or Distance Learning (PJJ) is very appropriate to implement during the Covid-19 pandemic as an effort so that the learning process can continue. This study aims to view differences in students' science learning outcomes in the energy source material between those using the Online and Offline Distance Learning systems. This type of research is quasi-experimental, with sample selection using sample probability with a simple random sampling method. The data collection instrument in this study used a test and was analyzed using a two-way ANOVA test. The result of data analysis showed that there significant differences between the science learning outcomes of elementary school students in the energy source materials using the match and offline systems. The results showed that the average score obtained by the group of elementary school students who taught using the Online Distance Learning system, which was 78.41, was higher than the average score obtained by the group of students taught by the Offline Distance Learning system, which was 72.66. Based on the average value of the two treatments, it can be interpreted that the learning outcomes of elementary school students using the Online Distance Learning system are better compared to the learning outcomes of elementary students using the Offline Distance Learning system for science learning outcomes. This research can be developed by educators at the elementary school level to maximize distance learning from home learning to increase elementary school students' knowledge during the Covid-19 pandemic.